Energy positive neighborhoods and smart energy districts : methods, tools, and experiences from the field - Monti, Antonello; Pesch, D. (Dirk); Ellis, K. A. (Keith A.); Mancarella, Pierluigi (Academic Press, 2017)
This book explores the processes and tools involved in creating energy positive neighborhoods and smart energy districts in an urban setting.